Retrospective review of the incidence of venous thromboembolism in pregnancy and the puerperium and identification of presenting complaints of pregnancy-related venous thromboembolism at Groote Schuur Maternity Centre, Cape Town between 1 January 2016 and 31 December 2016 - Montgomery, Colin Jaco (Department of Obstetrics and Gynaecology, 2020)
Background: Venous thromboembolism is one of the leading causes of morbidity and mortality around the world. In addition to the immediate morbidity, there is significant implications on delivery plans, future options of contraception and thromboprophylaxis in subsequent pregnancies. At present, no pre-test probability assessments are being used to predict venous thromboembolism in pregnancy. This is the first study in South-Africa, addressing venous thromboembolism in the perinatal period which specifically examines the epidemiology and clinical presentation in pregnancy and the post-partum period. Objectives: To determine the incidence of venous thromboembolism in Groote Schuur Maternity Centre and to identify specific variables in the clinical presentation that had a predictive value of a thromboembolic event. Methods: A quantitative, retrospective study with a descriptive comparative research design, for a twelve-month period from January 2016 to December 2016. All pregnant and postpartum patients who were sent for a venous duplex ultrasound, ventilation perfusion study or computerized tomography pulmonary angiogram from the Groote Schuur Maternity center were included. A folder review was conducted and the diagnosis and clinical presentation of all the patients were documented and analyzed. Incidence of VTE were estimated as the number of events per 1,000 deliveries. The number of hospital deliveries in 2016 were used as the denominator for calculating this incidence. Results: A total of 41 (0.12%) patients had a venous thromboembolism. Six patients had a deep venous thrombosis (0.02%) and 37 had a pulmonary embolism (0.11%). Among the 186 retrieved medical records, 11 (28%) of the diagnosis occurred in the puerperal period and 28 (72%) during pregnancy. Among the 28 events during pregnancy, one (3%) was in the first trimester, nine (23%) in the second trimester and 18 (46%) in the third trimester. The majority of confirmed pulmonary emboli (72.22%) and deep venous thrombosis (66.67%) were diagnosed during the third trimester in pregnancy. Among individuals with deep venous thrombosis, the most frequently reported symptoms and signs were leg pain (66.7%), leg swelling (66.7%) and tachycardia (66.7%). Patients without deep venous thrombosis presented more with leg swelling (76.3%), red discolouration (10.5%) and cellulites (10.5%). The only presenting clinical features that were significantly different were haemoptysis (p=0.01) and coughing (p=0.03). Among those individuals without pulmonary embolus, tachycardia (77.3%) and dyspnoea (49.1%) were commonly reported. Among the patients with a PE, the most frequently reported symptoms were tachypnoea (78.4%), dyspnoea (64.9%), tachycardia (62.2%), chest pain (51.4%) and coughing (46%). Features in the clinical presentation that were statistically significant were chest pain (p=0.01), haemoptysis (p=0.07), tachypnoea (p=0.01) and tachycardia (p=0.03). The greatest statistically significant clinical feature was the symptom of coughing (p< 0.01). The stepwise logistic regression for the univariate analysis showed that coughing (OR=3.83; 95% CI: 1.71 to 8.58; P< 0.01), chest pain (OR=2.57; 95% CI: 1.2-5.53; P=0.02), tachycardia (OR=1.03; 95% CI: 1.0 to 1.06; P=0.03), tachypnoea (OR=1.06; 95% CI: 1.0 to 1.12; P=0.05) and a median symptom of 3.5 (1.58; 95% CI: 1.23 to 2.06; P< 0.01) were the best explanatory variables. The stepwise logistic regression for the multivariate analysis showed that both tachycardia (OR=1.03; 95% CI: 1.0 to 1.06; P=0.03) and coughing (OR=3.43; 95% CI: 0.88 to 11.30; P=0.05) predicted a positive pulmonary embolus. A logistic regression for tachycardia showed a 23% increase in pulmonary embolus for every increase of 5 beats per minute in the heart rate above 100Bpm. This association was statistically significant (OR=1.23; 95% CI:1.08 to 1.39; P=0.0004) A logistic regression analysis of the association between tachycardia, tachypnoea and chest pain and the risk of having a pulmonary embolus showed a 4% increase in the risk of pulmonary embolus for every single unit increase in heart rate. When controlling for tachycardia and tachypnoea, chest pain was also associated with a 3.8 times increase in the odds of having a pulmonary embolus. This association was statistically significant (p=0.0002) Conclusion: In this study, we found that the incidence of venous thromboembolism in the Groote Schuur Maternity Centre was the same as in other developed and developing countries around the world. The majority of confirmed venous thromboembolisms were diagnosed during the third trimester in pregnancy. This study found a lower incidence of deep venous thrombosis in comparison to other studies. The clinical features that had some predictive value for pulmonary embolism were chest pain, coughing, tachypnoea, tachycardia and more than three symptoms or signs. Tachycardia was significant in the univariate-, multivariate analysis and stepwise logistic regression. In addition, there was a statistically significant association between tachycardia, tachypnoea and chest pain and the risk of having a pulmonary embolus. This study has revealed the need to develop pre-assessment algorithms in pregnancy and postpartum patients to reduce maternal and fetal, morbidity and mortality. Until such algorithms are developed, clinicians should use their own clinical judgment and proceed to diagnostic imaging for suspected VTE, where indicated.